Highly Selective Mercury Detection at Partially Oxidized Graphene/Poly(3,4-Ethylenedioxythiophene):Poly(Styrenesulfonate) Nanocomposite Film-Modified Electrode - Yasri, Nael G.; Sundramoorthy, Ashok K.; Chang, Woo-Jin; Gunasekaran, Sundaram (Frontiers in Materials, 2014)
Partially oxidized graphene flakes (po-Gr) were obtained from graphite electrode by an electrochemical exfoliation method. As-produced po-Gr flakes were dispersed in water with the assistance of poly(3,4-ethylenedioxythiophene)/poly(styrenesulfonate) (PEDOT:PSS). The po-Gr flakes and the po-Gr/PEDOT:PSS nanocomposite (po-Gr/PEDOT:PSS) were characterized by Raman spectroscopy, Fourier transform-infrared spectroscopy (FT-IR), UV-Vis spectroscopy, X-ray diffraction (XRD) and scanning electron microscopy (SEM). In addition, we demonstrated the potential use of po-Gr/PEDOT:PSS electrode in electrochemical detection of mercury ions (Hg2+) in water samples. The presence of po-Gr sheets in PEDOT:PSS film greatly enhanced the electrochemical response for Hg2+. Cyclic voltammetry measurements showed a well-defined Hg2+ redox peaks with a cathodic peak at 0.23 V, and an anodic peak at 0.42 V. Using differential pulse stripping voltammetry, detection of Hg2+ was achieved in the range of 0.2 to 14 µM (R2 = 0.991), with a limit of detection (LOD) of 0.19 µM for Hg2+. The electrode performed satisfactorily for sensitive and selective detection of Hg2+ in real samples, and the po-Gr/PEDOT:PSS film remains stable on the electrode surface for repeated use. Therefore, our method is potentially suitable for routine Hg2+ sensing in environmental water samples.